Lifestyle Medicine and Sleep Quality in Medical Students: Medicina del estilo de vida y calidad del sueño en estudiantes de medicina - Allende-Rayme, Fiorella Rosemary (2021)
Maintaining a good sleep quality is a basic human need, because the poor sleep is associated with negative effects such as exhaustion, uncontrolled emotions, the inability to concentrate, the inability to remember or think clearly, poor university and work performance, psychological and academic stress, anxiety, depression and difficulty in resolving problems; also long-term effects such as cardiovascular diseases, diabetes mellitus type II, obesity, cancer, among others.